An Analysis of Reflective Teaching Journal about Classroom Management (CM) By Students’ Teachers in Their Practice of Teaching Internship - Intani Ratu Maulina; Endang Komariah; Nira Erdiana (Universitas Syiah Kuala, 2021)
Teaching internship program are designed to smooth the transition from students to teachers. And classroom management is one of the important factors that should be mastered by the students’ teachers to control and overcome the problems in the classroom. This study aims at investigating how do the students’ teachers manage the class in their practice teaching internship program. This research utilized descriptive qualitative research. There were ten students’ teachers that involved as participants in this research. The data were collected through (1) self-reflections of the students’ teachers and (2) interview which sought the information about the student teachers’ in managing classroom management. The results of reflective teaching journal with instruments; the document and interview that is identifying based on Danielson’ framework, most of the students’ teachers are succeeded in managing classroom in their practice teaching internship. The result of document, including; in management of instructional groups there are six students teachers they are in distinguished level, in the management of transition there are eight students teachers are at the distinguished level, in management of materials and supplies, all of the students’ teachers are at a distinguished level, In the performance of non-instructional duties the researcher identified, three students teachers in distinguished level. Therefore, the researcher concluded that the students teachers succeeded in managing classroom management.